(untitled) (Journal Of Educational and Psychological Researches, 2022)
With the premise that effective use of online instructional practices is of vital importance in classrooms, the current study aimed to examine the effects of using Moodle applications to develop instructors’ skills in designing electronic tests at Dhofar University. The sample of this study consisted of (25) instructors participated in the experimental group. The researchers implemented a quasi-experimental design with one group pre- and post-test; in addition, an observation card was implemented to measure the target skills related to test design. The research instruments were subjected to validity and reliability measures to ensure valid and reliable data and results. The study results showed that those instructors who participated in the experimental group were improved in designing electronic test using the Moodle platform. The main recommendation in this study is the importance to train instructors in all colleges of Dhofar University and rising their level of interest in using the Moodle system, designing, and implementing electronic tests and their applications to the university students at the undergraduate and graduate programs.